1992
DOI: 10.1007/bf00341221
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the effluent volume in high-output ileostomy patients by a somatostatin analogue, SMS 201-995

Abstract: Twelve ileostomy patients were given subcutaneous SMS 201-995 therapy (100 micrograms t.d.s. for 5 days) in a randomized placebo-controlled trial. All patients had ileostomies constructed 60 cm proximal to the terminal ileum (proximal ileostomy) following restorative proctocolectomy. SMS 201-995 reduced the daily ileostomy output from 997 +/- 52 g to 736 +/- 28 g, P < 0.05, along with a decrease in daily sodium and chloride excretion (sodium: 92.60 +/- 8.51 to 75.22 +/- 8.64 mEq, chloride: 143.46 +/- 8.54 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…[111][112][113][114][115][116][117][118][119] The greatest reductions in intestinal output are in those with a net secretory output, and the volume of parenteral supplements needed may be reduced. [115][116][117][118][119] The reduction in sodium output parallels that of intestinal output 111-119 while magnesium balance is unchanged.…”
Section: N Antisecretory Drugsmentioning
confidence: 99%
“…[111][112][113][114][115][116][117][118][119] The greatest reductions in intestinal output are in those with a net secretory output, and the volume of parenteral supplements needed may be reduced. [115][116][117][118][119] The reduction in sodium output parallels that of intestinal output 111-119 while magnesium balance is unchanged.…”
Section: N Antisecretory Drugsmentioning
confidence: 99%
“…Octreotide has a serum halflife of 90 minutes so is given as regular (two or three time's daily) subcutaneous injections before food. Several studies in adults have shown octreotide to reduce ileostomy diarrhoea and large volume jejunostomy outputs [100,[107][108][109][110][111][112][113][114] . The greatest reductions in intestinal output have occurred in net "secretors", and many patients have been able to reduce the volume of parenteral supplements needed [110,114] .…”
Section: Antisecretory Drugsmentioning
confidence: 99%
“…The greatest reductions in intestinal output have occurred in net "secretors", and many patients have been able to reduce the volume of parenteral supplements needed [110,114] . All studies have shown a reduction in sodium output, which parallels that of the intestinal output [100,[107][108][109][110][111][112][113][114] . Magnesium balance has not been changed by octreotide [107,112] .…”
Section: Antisecretory Drugsmentioning
confidence: 99%
“…Management of a HOS includes the identification and treatment of any cause for the high output, reduction and replacement of water and electrolyte losses [initially via the intravenous (iv) route], oral hypotonic fluid restriction with the use of glucose ⁄ electrolyte solution [9,11,12], anti diarrhoeal [13][14][15] and anti secretory medication [9,[16][17][18][19][20][21][22][23], nutritional support, wound care and psychological support.…”
Section: Introductionmentioning
confidence: 99%